Influence of Ownership on Pre-Service Teachers’ Level of ICT Needs in Colleges of Education in North Central, Nigeria - ANAZA, Abdulmumuni Onuyi (Ilorin Journal of Education, 2023)
The world is presently characterised by change in all areas of the society and this is occasioned by development in the realm of Information and Communication Technology (ICT). This study examined influence of ownership on pre-service teachers’ level of ICT needs in colleges of education in north central Nigeria. For the study, six research questions and hypotheses were developed. This study used descriptive survey type of research design. The target audience was pre-service teachers at colleges of education in the north central states of Nigeria. A random sample of 1,360 pre-service teachers from 11 colleges of education was taken. The instrument for this study was adapted from UNESCO's ICT- CFT with title “Student-Teachers ICT Needs in Colleges of Education” (STICTNCOE). The items on the questionnaire were based on the six levels of UNESCO ICT-CFT at the Technology Literacy approach. The questionnaire possessed reliability coefficient of 0.86. Based on the Technology Literacy approach of UNESCO ICT-CFT, the study's findings showed that ownership had no influence on pre-service teachers' level of ICT needs in colleges of education. It also showed that there were no significant differences between federal and state colleges of education regarding the level of ICT needs of pre-service teachers in North Central colleges of education in their understanding of ICT in education, curriculum and assessment, pedagogy, ICT integration, organization and administration, and professional learning. It was recommended that ICT projects should benefit colleges of education - federal, state or private from designated agencies such as Tetfund.